Uji Antidiare Granul dari Ekstrak Etanol Daun Kratom (Mytragina specioca Korth) terhadap Mencit Putih Jantan (Mus musculus L) - Suhaimi Suhaimi; Dian Kartikasari (JURNAL ILMU KEFARMASIAN INDONESIA, 2020)
Indonesian medicinal plants have been used as traditional medicine (herbal medicine), standardized herbal medicines or phytopharmaca. Kratom leaf ethanol (Mitragyna speciose Korth) has Escherichia coli bacterial activity with a concentration of 5%. Kratom leaf extract granules. Ethanol extract of kratom leaf (Mitragyma specioca Korth) has activity against male white mice (Mus musculus L) as antidiarrheal and know the time used for granules of kratom leaf ethanol extract (Mitragyma specioca Korth) and the dosage which gives activity to white mice (Mus musculus L) as antidiarrheal and know the time used for granules of kratom leaf ethanol extract (Mitragyma specioca Korth) and the dosage which gives activity to white mice (Mus musculus L) as antidiarrheal, Kratom leaf extract granule was tested to white male mice with a concentration without active substance (blank) formula 1 as a negative control and using active ingredient kratom leaf extract formula II using a concentration of 0.4%, Formula III concentration 0.5 % and formula IV with a concentration of 0.6% using loperamid HCL as a positive control Method of randomized block design (True Experimental Post Only Control Group) 6 hours of observation time with variations seen were organoleptic, consistency, frequency and stool weight. kratom 0.4% has antidiarrheal activity with a time of 330 minutes.